In situ enzymatic formation of supramolecular nanofibers for efficiently killing cancer cells. Issue 39 (1st April 2016) - Huang, Anqing; Ou, Caiwen; Cai, Yanbin; Wang, Zhongyan; Li, Hekai; Yang, Zhimou; Chen, Minsheng
Abstract : Precursors were more toxic to cancer cells than their corresponding gelators. Abstract : We report a strategy of in situ forming supramolecular nanofibers of taxol-phosphorylated peptide conjugates catalyzed by phosphatase for efficiently killing cancer cells.